Kepercayaan dan Pengobatan Rufaidah Karya Ahmad Syauqi Al-Fanjari: Kajian Sosiologi Sastra - Ulyah Darajah (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
The purpose of this research is to describe how public belief and treatment during the Jahiliyah period and when Islam entered into was carried out by a nurse named Rufaidah in the book Rufaidah written by Ahmad Syauqi al-Fanjari with the perspective of literary sociology. The method in this research is descriptive qualitative analysis method. Sociology of literature is considered effective to find out how the belief and treatment of the Islamic period carried out by Rufaidah. The result of this research is people who believe and worship the statues and gods, because they consider the gods who give them everything, both in terms of health, daily life and even about the future. But after the entry of Islam their thinking changed and they were so confident in Islam, even they were always careful in doing anything. The treatment process carried out by Rufaidah from before converting to Islam is changing, from a treatment that does not pay attention to cleanliness and humanity turned into a treatment that is clean, holy and humane. Rufaidah's treatment is done in Rufaidah's book as an herbal treatment at this time.